Quantitative Muscle Analysis in FSHD Using Whole-Body Fat-Referenced MRI: Composite Scores for Longitudinal and Cross-sectional Analysis. (30th August 2022) - Mellion, Michelle L.; Widholm, Per; Karlsson, Markus; Ahlgren, André; Tawil, Rabi; Wagner, Kathryn R.; Statland, Jeffrey M.; Wang, Leo; Shieh, Perry B.; van Engelen, Baziel G.M.; Kools, Joost; Ronco, Lucienne; et al.
Abstract : Background and Objectives: Facioscapulohumeral muscular dystrophy (FSHD) is a rare, debilitating disease characterized by progressive muscle weakness. MRI is a sensitive assessment of disease severity and progression. We developed a quantitative whole-body (WB) musculoskeletal MRI (WB-MSK-MRI) protocol analyzing muscles in their entirety. This study aimed to assess WB-MSK-MRI as a potential imaging biomarker providing reliable measurements of muscle health that capture disease heterogeneity and clinically meaningful composite assessments correlating with severity and more responsive to change in clinical trials. Methods: Participants aged 18–65 years, with genetically confirmed FSHD1, clinical severity 2 to 4 (Ricci scale, range 0–5), and ≥1 short tau inversion recovery–positive lower extremity muscle eligible for needle biopsy, enrolled at 6 sites and were imaged twice 4–12 weeks apart. Volumetric analysis of muscle fat infiltration (MFI), muscle fat fraction (MFF), and lean muscle volume (LMV) in 18 (36 total) muscles from bilateral shoulder, proximal arm, trunk, and legs was performed after automated atlas-based segmentation, followed by manual verification. A WB composite score, including muscles at highest risk for progression, and functional cross-sectional composites for correlation with relevant functional outcomes including timed up and go (TUG), FSHD-TUG, and reachable workspace (RWS), were developed. Results: Seventeen participants enrolled in this study; 16 follow-up MRIs were performed at 52 days (range 36–85 days). Functional cross-sectional composites (MFF and MFI) showed moderate to strong correlations: TUG (ρ = 0.71, ρ = 0.83), FSHD-TUG (ρ = 0.73, ρ = 0.73), and RWS (left arm: ρ = −0.71, ρ = −0.53; right arm: ρ = −0.61, ρ = −0.65). WB composite variability: LMVtot, coefficient of variation (CV) 1.9% and 3.4%; MFFtot, within-subject SD (Sw ) 0.5% and 1.5%; and MFItot (Sw ), 0.3% and 0.4% for normal and intermediate muscles, respectively. CV and Sw were higher in intermediate (MFI ≥0.10; MFF <0.50) than in normal (MFI <0.10, MFF <0.50) muscles. Discussion: We developed a WB-MSK-MRI protocol and composite measures that capture disease heterogeneity and assess muscle involvement as it correlates with FSHD-relevant clinical endpoints. Functional composites robustly correlate with functional assessments. Stability of the WB composite shows that it could be an assessment of change in therapeutic clinical trials. Classification of Evidence: This study provides Class II evidence that quantitative WB-MSK-MRI findings associate with FSHD1 severity measured using established functional assessments.